2022
DOI: 10.1080/0886022x.2022.2094806
|View full text |Cite
|
Sign up to set email alerts
|

Non-diabetic urine glucose in idiopathic membranous nephropathy

Abstract: This study aims to analyze the characteristics of idiopathic membranous nephropathy (iMN) with nondiabetic urine glucose during the follow-up. We retrospectively analyzed the data of 1313 patients who were diagnosed iMN. The prevalence of nondiabetic urine glucose during follow-up was 10.89%. There were significant differences between the patients with nondiabetic urine glucose and those without urine glucose in gender, hypertension ratio, proteinuria, N-acetyl-β-glucosaminidase, retinol binding protein, serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Patients with CKD showed varying degrees of impaired glucose tolerance [ 42 ]. In a cohort study of 1313 IMN patients, Cox regression showed that urinary glucose and baseline SCr were risk factors for a 50% reduction in eGFR [ 43 ]. The reason may be that with the progression of kidney disease, patients developed insulin resistance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD showed varying degrees of impaired glucose tolerance [ 42 ]. In a cohort study of 1313 IMN patients, Cox regression showed that urinary glucose and baseline SCr were risk factors for a 50% reduction in eGFR [ 43 ]. The reason may be that with the progression of kidney disease, patients developed insulin resistance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In observing GU, this study also showed significant differences in GU levels in the R. norvegicus group before and after injection of L-NAME, which were observed for five days of the experiment. One study showed that GU patients had higher proteinuria, serum creatinine, and a lower estimated glomerular filtration rate (eGFR) [27]. Other studies have shown that a history of PE may serve as an additional risk factor for gestational diabetes mellitus (GDM) in subsequent pregnancies, as GDM is independently associated with PE in singletons.…”
Section: -Discussionmentioning
confidence: 99%